Carbon-coated aluminum foil web and method of making the same
Patent Information
- Application Number
- CN202611297516.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]本发明提供了一种涂炭铝箔卷材及其制备方法,旨在克服逆涂方式下版辊网纹边缘对涂炭铝箔表面涂炭层造成的机械刮擦损伤,同时解决顺涂条件下易出现的缺料条纹以及胶粘剂边界内缩、流挂的问题,实现在涂炭铝箔表面高质量、高精度地涂覆胶粘剂功能涂层,并能够在同一涂布设备上兼顾全域满幅涂布与边缘局部选择性涂布
[0018] Compared with the prior art, the present invention, by rotating the micro-gravure roller in the same direction and with a similar linear speed as the carbon-coated aluminum foil strip during the forward coating process, eliminates the scraping and micro-cutting effect of the roller's mesh edge on the carbon coating surface during the reverse coating process, thus avoiding micro-cracks, scratches and local peeling on the carbon layer surface.
Smart Images

Figure CN122913041A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of coating process technology, specifically to a carbon-coated aluminum foil roll and its preparation method. Background Technology
[0002] Carbon-coated aluminum foil (or carbon-coated aluminum foil) has become one of the core current collector materials for power batteries and energy storage batteries because it coats the aluminum foil surface with a conductive carbon black layer, which can significantly reduce the internal resistance of lithium-ion batteries and improve the adhesion between the active material and the current collector.
[0003] To further enhance the safety, heat resistance, and edge insulation performance of carbon-coated aluminum foil, some technical solutions employ the method of coating an adhesive functional layer onto the carbon coating surface. For example, coating with a ceramic slurry (such as an alumina Al2O3 layer or boehmite layer) can provide insulation, heat resistance, and short-circuit prevention; coating with polyvinylidene fluoride (PVDF) adhesive can enhance the adhesion between the electrode and the separator; and coating with acrylic protective adhesive can improve the processing flexibility of the foil. The coating methods for these adhesives include full-coverage coverage and selective edge coverage.
[0004] However, when applying ceramic adhesive to the surface of carbonized aluminum foil, the reverse coating method reveals a series of insurmountable defects in actual production: During reverse coating, the textured edge of the printing roller forms high-speed relative sliding friction and micro-cutting action with the carbonized aluminum foil surface. This mechanical scraping damages the bonding interface between the carbon layer and the aluminum foil substrate, leading to micro-cracks, scratches, and even localized peeling on the carbon layer surface, reducing the conductivity and adhesion of the carbon layer. For ultra-thin carbonized layers (thickness ≤ 1 μm), the above problems are particularly serious, with the carbon layer damage rate reaching as high as 15%-30% under the reverse coating method, severely restricting the industrial application of high-performance ultra-thin carbonized aluminum foil.
[0005] Therefore, it is necessary to provide a new type of carbon-coated aluminum foil roll and its preparation method, so as to achieve high-quality and high-precision coating of adhesive functional coating without causing mechanical damage to the carbon coating layer, and to take into account both full-width coating and selective edge coating. Summary of the Invention
[0006] This invention provides a carbon-coated aluminum foil roll and its preparation method, aiming to overcome the mechanical scratch damage caused by the edge of the printing roller to the carbon coating layer on the surface of the carbon-coated aluminum foil under reverse coating, and at the same time solve the problems of material shortage stripes, adhesive boundary shrinkage and sagging that are prone to occur under forward coating. It achieves high-quality and high-precision coating of adhesive functional coating on the surface of carbon-coated aluminum foil, and can take into account both full-width coating and selective edge coating on the same coating equipment.
[0007] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a method for preparing carbon-coated aluminum foil rolls, the method comprising the following steps: Step S1: Install the carbon-coated aluminum foil master roll with conductive carbon coating on both sides onto the unwinding shaft of the unwinding device, control the unwinding tension of the carbon-coated aluminum foil strip after it is unwound from the carbon-coated aluminum foil master roll to be 50~120N / m, and flatten the carbon-coated aluminum foil strip before it enters the coating station. Step S2: Obtain the adhesive and the unidirectional coating microgravure roller. The unidirectional coating microgravure roller includes a roller body and a working layer disposed on the surface of the roller body. The surface of the working layer is provided with a coating functional area. The surface of the coating functional area is engraved with a mesh structure. The mesh depth of the mesh structure is 12~30μm and the mesh line count is 200~300 lines / inch. The adhesive is supplied to the coating functional area, and the rotation direction of the unidirectional coating micro-gravure roller is set in the same direction as the travel direction of the carbon-coated aluminum foil strip. The adhesive is carried by the textured structure, and during the process of the unidirectional coating micro-gravure roller and the carbon-coated aluminum foil strip moving in the same direction, the adhesive is transferred to the conductive carbon coating surface on at least one side of the carbon-coated aluminum foil strip to form a wet adhesive coating. Step S3: The carbonized aluminum foil strip with the adhesive wet coating is fed into an oven and dried using a gradient heating method. During drying, the carbonized aluminum foil strip passes sequentially through a first temperature zone and a second temperature zone. The temperature of the first temperature zone is 70-100°C, and the residence time of the carbonized aluminum foil strip in the first temperature zone is 1-3 minutes to evaporate the solvent or moisture in the adhesive wet coating. The temperature of the second temperature zone is 80-150°C, and the residence time of the carbonized aluminum foil strip in the second temperature zone is 1-3 minutes to allow the adhesive wet coating to crosslink and cure, forming a functional coating. Step S4: Inspect the dried carbon-coated aluminum foil strip and rewind the qualified carbon-coated aluminum foil strip to obtain carbon-coated aluminum foil roll.
[0009] Preferably, the unidirectional microgravure roller is a full-width coating roller, and the mesh structure is uniformly distributed along the axial direction of the working layer within the coating functional area; the adhesive wet coating covers the entire coating area of the carbon-coated aluminum foil strip.
[0010] Preferably, the unidirectional coating microgravure roller is a selective coating roller, and the surface of the working layer is divided along the axial direction of the unidirectional coating microgravure roller into a non-coating area located in the middle of the unidirectional coating microgravure roller and coating areas located on both sides of the non-coating area. The surface of the coating area is engraved with the mesh structure, and the surface of the non-coating area is a mirror structure with a roughness of less than or equal to 0.15μm. At the boundary between the coating area and the uncoated area, a gradient transition zone with a gradually changing mesh depth is provided. The mesh depth in the gradient transition zone gradually decreases from the mesh depth of the coating area towards the uncoated area along the axial direction of the unidirectional coating micro-gravure roller to zero. During coating, the coating area transfers the adhesive to both sides of the carbonized aluminum foil strip, forming a blank area in the middle of the carbonized aluminum foil strip that is not coated with the adhesive.
[0011] Preferably, step S2 includes the following steps: adjusting the angle between the axis of the unidirectional coating microgravure roller and the plane where the carbonized aluminum foil strip is located to 2~8°, controlling the ratio of the linear velocity of the unidirectional coating microgravure roller to the linear velocity of the carbonized aluminum foil strip to be 0.9~1.1:1, and the traveling speed of the carbonized aluminum foil strip to be 15~60m / min.
[0012] Preferably, the diameter of the unidirectional coating microgravure roller is 150~220mm, and the dynamic balance quality grade of the unidirectional coating microgravure roller is greater than or equal to G6.3.
[0013] Preferably, the working layer has a thickness of 50~200μm and a hardness greater than or equal to HV950.
[0014] Preferably, the adhesive has a viscosity of 200~3500cps, a thixotropic index of 2~7, and a fineness of ≤5μm; wherein the thixotropic index is the ratio of the viscosity at 6rpm to the viscosity at 60rpm under the same conditions.
[0015] Preferably, the adhesive is prepared before step S2; by weight, the adhesive comprises 10-55 parts of functional components, 5-30 parts of binder, 0.3-3 parts of thixotropic agent, 0.5-2.5 parts of wetting and dispersing agent, and the balance being deionized water or organic solvent, wherein the sum of the weight parts of each component is 100 parts.
[0016] Preferably, the functional component is one or more of ceramic powder, polyvinylidene fluoride resin, or acrylic resin; the thixotropic agent is hydroxyethyl cellulose or bentonite.
[0017] Secondly, the present invention also provides a carbon-coated aluminum foil roll, which is made by the preparation method of carbon-coated aluminum foil roll as described in any of the above embodiments.
[0018] Compared with the prior art, the present invention, by rotating the micro-gravure roller in the same direction and with a similar linear speed as the carbon-coated aluminum foil strip during the forward coating process, eliminates the scraping and micro-cutting effect of the roller's mesh edge on the carbon coating surface during the reverse coating process, thus avoiding micro-cracks, scratches and local peeling on the carbon layer surface.
[0019] The present invention enables the adhesive to spread laminarly and naturally level on the coating surface under low shear force in convex coating, which helps to eliminate flow marks, orange peel texture and microbubble pinhole defects commonly found in reverse coating, resulting in excellent surface quality of the adhesive coating.
[0020] This invention addresses the issue of material shortage streaks that often occur in unidirectional coating by adjusting the structure of the microgravure roller. The shallow mesh of 12-30μm ensures that the adhesive can be completely demolded and transferred under the low shear force of unidirectional coating, while the high mesh count of 200-300LPI ensures that the coating is dense and uniform. The two factors work together to solve the problem of material shortage streaks that often occur in unidirectional coating.
[0021] The present invention sets the thixotropic index of the adhesive to 2-7, which thins under shear during mesh filling, making it easy to fill, and quickly recovers high viscosity after being transferred to foil, which can prevent coating boundary shrinkage and sagging, and ensure coating boundary accuracy.
[0022] This invention allows for flexible switching between full-width coating and edge selective coating modes on the same coating equipment by replacing the coating rollers with different structures (full-width coating rollers or selective coating rollers). No mechanical modifications to the coating machine are required, which helps reduce equipment investment costs. Attached Figure Description
[0023] The present invention will now be described in detail with reference to the accompanying drawings. The above and other aspects of the present invention will become clearer and more readily understood through the detailed description following the accompanying drawings. In the drawings: Figure 1 This is a flowchart of the preparation method of carbon-coated aluminum foil roll provided in the embodiments of the present invention; Figure 2 This is a schematic diagram of the structure of the unidirectional microgravure roller in the method for preparing carbon-coated aluminum foil rolls provided in this embodiment of the invention; Figure 3 This is a schematic diagram of the structure of the unidirectional micro-gravure roller in the method for preparing carbon-coated aluminum foil rolls provided in this embodiment of the invention when it is a full-width coating roller; Figure 4 This is a schematic diagram of the structure of the sequential coating microgravure roller in the method for preparing carbon-coated aluminum foil rolls provided in this embodiment of the invention, when it is a selective coating roller.
[0024] In the diagram, 10 is the unidirectional micro-gravure roller; 01 is the roller body; 02 is the working layer; 03 is the textured structure; 04 is the coating area; and 05 is the non-coating area. Detailed Implementation To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0025] Implementation Method 1 Please refer to Figures 1 to 2 This invention provides a method for preparing carbon-coated aluminum foil rolls, the method comprising the following steps: Step S1: Install the carbon-coated aluminum foil master roll with conductive carbon coating on both sides onto the unwinding shaft of the unwinding device, control the unwinding tension of the carbon-coated aluminum foil strip after it is unwound from the carbon-coated aluminum foil master roll to be 50~120N / m, and flatten the carbon-coated aluminum foil strip before it enters the coating station.
[0026] In this embodiment of the invention, because the carbon-coated aluminum foil strip is relatively thin (e.g., 12~15μm), its mechanical strength is low: if the unwinding tension is too high, the strip is easily stretched and deformed or even broken; if the unwinding tension is too low, the strip is loose and prone to wrinkles, both of which affect the uniformity of coating. This invention controls the unwinding tension at 50~120N / m and, in conjunction with strip flattening, allows the strip to enter the coating station in a flat and stable state, which helps ensure the uniformity of the thickness of the subsequent wet adhesive coating. Step S2: Obtain the adhesive and the unidirectional coating microgravure roller 10. The unidirectional coating microgravure roller 10 includes a roller body 01 and a working layer 02 disposed on the surface of the roller body 01. The surface of the working layer 02 is provided with a coating functional area. The surface of the coating functional area is engraved with a mesh structure 03. The mesh depth of the mesh structure 03 is 12~30μm, the mesh line count is 200~300 lines / inch (LPI), and the mesh structure 03 is a frustum pyramid shape. During coating, the adhesive can be supplied to the coating functional area through a closed feeding system, and the rotation direction of the forward coating micro-gravure roller 10 is set in the same direction as the travel direction of the carbon-coated aluminum foil strip, that is, forward coating is performed. The adhesive is carried by the textured structure 03, and during the process of the forward coating micro-gravure roller 10 and the carbon-coated aluminum foil strip moving in the same direction, the adhesive is transferred to the conductive carbon coating surface on at least one side of the carbon-coated aluminum foil strip to form a wet adhesive coating.
[0027] In this embodiment of the invention, under the above-mentioned forward coating method, the forward coating micro-gravure roller 10 and the carbon-coated aluminum foil strip move in the same direction. Especially when the linear velocities of the two are close, there is no high-speed relative sliding between the mesh edge of the mesh structure 03 and the conductive carbon coating. This fundamentally avoids the scratching and micro-cutting effect of the mesh edge on the carbon coating surface in the reverse coating method, which helps to achieve zero mechanical damage to the conductive carbon coating, thereby ensuring the conductivity of the conductive carbon coating and the adhesion between the conductive carbon coating and the aluminum foil substrate. For ultra-thin carbon-coated aluminum foil with a carbon coating thickness of no more than 1 μm, the above-mentioned effect of avoiding mechanical damage is particularly significant.
[0028] Meanwhile, the low-shear environment of convex coating allows the adhesive to spread laminarly and naturally level on the strip surface, helping to eliminate surface defects such as flow marks, orange peel texture, and microbubbles and pinholes common in reverse coating, thus improving the appearance quality of the functional coating. Furthermore, the shallow mesh structure with a depth of 12~30μm ensures complete demolding and transfer of the adhesive under the low shear force of convex coating, while the high line count of 200~300 lines / inch guarantees a dense and uniform coating. These two factors work together to avoid short-stripe patterns caused by insufficient adhesive supply under convex coating conditions. The use of a closed-loop feeding system also reduces viscosity fluctuations caused by solvent evaporation, ensuring feeding stability during the coating process.
[0029] Please refer to Figure 3 In some embodiments, the unidirectional microgravure roller 10 is a full-width coating roller, and the anilox structure 03 is uniformly distributed along the axial direction of the unidirectional microgravure roller 10 within the coating functional area. During coating, the adhesive wet coating layer covers the entire coating area 04 of the carbon-coated aluminum foil strip, achieving full-width coating. Furthermore, the anilox structure 03 can be a frustum-shaped cell, with through grooves between adjacent cells; these through grooves facilitate the homogenization of adhesive flow between adjacent cells, resulting in a continuous, dense, and uniformly thick coating formed by full-width coating.
[0030] Please refer to Figure 4 In other embodiments, the unidirectional coating microgravure roller 10 is a selective coating roller, and the surface of the working layer 02 is divided along the axial direction of the unidirectional coating microgravure roller 10 into a non-coating area 05 located in the middle of the unidirectional coating microgravure roller 10 and coating areas 04 located on both sides of the non-coating area 05. The surface of the coating area 04 is engraved with the mesh structure 03, and the surface of the non-coating area 05 is a mirror structure with a roughness of less than or equal to 0.15μm. At the junction of the coating area 04 and the uncoated area 05, a gradient transition zone with a gradually changing mesh depth is provided. The width of the gradient transition zone can be 0.5~1.2mm. The mesh depth in the gradient transition zone gradually decreases from the mesh depth of the coating area 04 towards the uncoated area 05 along the axial direction of the unidirectional coating micro-gravure roller to zero. During coating, the coating area 04 transfers the adhesive to both sides of the carbonized aluminum foil strip, so that a blank area without adhesive is formed in the middle of the carbonized aluminum foil strip.
[0031] In the aforementioned selective coating roller, since the uncoated area 05 has a mirror-like structure and no cavities, it does not carry adhesive during the coating process, ensuring no adhesive leakage in the blank area in the middle of the strip. The gradient transition zone makes the mesh depth change smoothly at the boundary between the coated area 04 and the uncoated area 05, avoiding material accumulation or thick edges at the coating boundary due to abrupt changes in mesh depth. This helps to form a clear, leak-free, and thick-edge-free edge coating, thereby achieving edge insulation coating of carbon-coated aluminum foil. In addition, by changing between the full-width coating roller and the selective coating roller, flexible switching between full-width coating and edge selective coating modes can be achieved on the same coating equipment without mechanical modification to the coating machine, which helps to reduce equipment investment costs.
[0032] In this embodiment of the invention, step S2 includes the following steps: adjusting the angle between the axis of the unidirectional coating microgravure roller 10 and the plane containing the carbon-coated aluminum foil strip to 2~8°, controlling the ratio of the linear velocity of the unidirectional coating microgravure roller 10 to the linear velocity of the carbon-coated aluminum foil strip to 0.9~1.1:1, and the traveling speed of the carbon-coated aluminum foil strip to 15~60m / min. Wherein, an excessively large angle will cause the carbon-coated aluminum foil strip to over-cover the unidirectional coating microgravure roller 10, easily leading to roller sticking. Controlling the angle to 2~8° can balance the adhesive transfer efficiency and the requirement for preventing roller sticking. When the ratio of the linear velocity of the carbon-coated aluminum foil strip to the unidirectional coating microgravure roller 10 is controlled at 0.9~1.1:1, their linear velocities are close, with almost no relative slippage, which can further eliminate mechanical friction damage to the conductive carbon coating caused by the roller.
[0033] In this embodiment of the invention, the diameter of the unidirectional coating microgravure roller 10 is 150~220mm, and the dynamic balance quality grade of the unidirectional coating microgravure roller 10 is greater than or equal to G6.3. The roller body 01 of the unidirectional coating microgravure roller 10 can be made of 45# seamless steel pipe and subjected to stress-relief annealing treatment. Stress-relief annealing can eliminate the internal stress of the roller body 01 during processing and prevent the roller from deforming after long-term use; a higher dynamic balance quality grade can ensure that the roller operates smoothly at high speed at a coating speed of 15~60m / min, avoiding defects such as periodic horizontal lines on the coating caused by roller vibration.
[0034] In this embodiment of the invention, the working layer 02 is an electroplated hard chrome layer with a thickness of 50~200μm and a hardness greater than or equal to HV950. The high hardness and good wear resistance of the electroplated hard chrome layer can reduce the wear of the mesh structure 03 during long-term continuous coating and extend the service life of the printing roller.
[0035] In this embodiment of the invention, the adhesive has a viscosity of 200-3500 cps, a thixotropic index of 2-7, and a fineness ≤5μm; wherein, the thixotropic index is the ratio of the viscosity at 6 rpm to the viscosity at 60 rpm under the same conditions. The aforementioned high thixotropic properties cause the adhesive to thin under shear stress during mesh filling, making it easy to fill, and it can quickly regain its high viscosity after being transferred to the strip surface. This helps prevent the adhesive from shrinking at the boundary or sagging due to gravity or capillary action under unidirectional coating conditions. A fineness of no more than 5μm prevents large particles in the adhesive from clogging the mesh cells or forming crystal points in the coating.
[0036] In this embodiment of the invention, a step of preparing the adhesive is included before step S2. The adhesive comprises, by weight, 10-55 parts of a functional component, 5-30 parts of a binder, 0.3-3 parts of a thixotropic agent, 0.5-2.5 parts of a wetting and dispersing agent, and the balance being deionized water or an organic solvent, wherein the sum of the weight parts of each component is 100 parts. The functional component can be one or more of ceramic powder (e.g., boehmite powder or alumina powder), polyvinylidene fluoride resin, or acrylic resin; the thixotropic agent can be hydroxyethyl cellulose or bentonite. It should be noted that when the functional component is a resin with inherent adhesive properties, such as polyvinylidene fluoride resin or acrylic resin, the functional component can simultaneously function as a binder. In this case, a separate binder may not be added to the formulation, or the amount of binder may be reduced accordingly.
[0037] In this embodiment of the invention, before coating in step S2, the surface of the conductive carbon coating can be pretreated with plasma. The power of the plasma pretreatment can be 600~800W, and the treatment time can be 8~10s. Plasma pretreatment can increase the surface energy of the conductive carbon coating and enhance the adhesion between the functional coating and the conductive carbon coating.
[0038] Step S3: The carbonized aluminum foil strip with the adhesive wet coating is fed into an oven and dried using a gradient heating method. During drying, the carbonized aluminum foil strip passes through a first temperature zone and a second temperature zone sequentially. The temperature of the first temperature zone is 70-100°C, and the residence time of the carbonized aluminum foil strip in the first temperature zone is 1-3 minutes to evaporate the solvent or moisture in the adhesive wet coating. The temperature of the second temperature zone is 80-150°C, and the residence time of the carbonized aluminum foil strip in the second temperature zone is 1-3 minutes to allow the adhesive wet coating to crosslink and cure, forming a functional coating.
[0039] In this embodiment of the invention, the temperature of the second temperature zone is higher than that of the first temperature zone; when the adhesive is a ceramic slurry, the temperature of the second temperature zone is preferably 120~150℃; when the adhesive is a polyvinylidene fluoride (PVDF) adhesive, the temperature of the second temperature zone is preferably 80~120℃. Furthermore, the oven can be a suspended oven to avoid damage to the wet coating caused by contact between the support components inside the oven and the surface of the strip during the drying process.
[0040] This invention employs a gradient heating drying process. The carbon-coated aluminum foil strip first undergoes a slow evaporation of solvent or moisture in a lower temperature zone, which avoids defects such as premature skinning, internal blistering, or pinholes caused by rapid solvent evaporation. Then, in a higher temperature zone, the adhesive is fully cross-linked and cured, which helps to form a dense and firmly bonded functional coating.
[0041] Step S4: Inspect the dried carbon-coated aluminum foil strip and rewind the qualified carbon-coated aluminum foil strip to obtain carbon-coated aluminum foil roll.
[0042] In this embodiment of the invention, a charge-coupled device (CCD) vision inspection system can be used to monitor the coverage width of the adhesive layer (in selective coating mode) and appearance defects online, and the qualified strips can be wound up at a set tension. Online inspection can promptly remove products with coating defects, which helps to ensure the quality consistency of carbon-coated aluminum foil roll products.
[0043] Implementation Method 2 This invention also provides a carbon-coated aluminum foil roll, which is made by the carbon-coated aluminum foil roll preparation method described in the above embodiments and can achieve the same technical effect. Please refer to the description in the above embodiments, which will not be repeated here.
[0044] The preparation method described above will be further explained in detail below with reference to specific embodiments.
[0045] Example 1 A 15μm thick aluminum foil with a 2μm double-sided carbon coating was selected, with a foil width of 486.4mm. The master roll of the carbon-coated aluminum foil was mounted on the unwinding shaft, and the unwinding tension was set to 80N / m. A full-width coating roller with a diameter of Φ200mm was selected. The anilox structure 03 was a frustum pyramid shape, with an anilox depth of 25μm and an anilox line count of 280 lines / inch. The surface of the coating functional area was uniformly engraved, and the working layer 02 was an electroplated hard chrome layer with a hardness of HV950. The roller was mounted on a microgravure coating machine, with the roller rotation direction set to be the same as the strip travel direction (co-coating), the angle between the roller axis and the plane of the strip being 4°, the ratio of the roller linear speed to the strip linear speed being 1.0:1, and the strip travel speed being 40m / min.
[0046] Preparation of ceramic coating slurry: 40 parts by weight of boehmite powder, 10 parts by weight of aqueous styrene-acrylic acid copolymer emulsion (functional component), 0.8 parts by weight of hydroxyethyl cellulose thixotropic agent, 1.2 parts by weight of sodium polyacrylate dispersant, and 48 parts by weight of deionized water were mixed thoroughly. The resulting ceramic slurry had a viscosity of 1800 cps, a thixotropic index of 4.8, and a fineness of 3 μm. Before coating, the strip surface was pretreated with plasma at a power of 800 W for 8 seconds. After coating, the strip was subjected to gradient drying, sequentially passing through a first temperature zone of 90℃ for 2 minutes and a second temperature zone of 130℃ for 2 minutes.
[0047] Testing revealed that the dry thickness of the ceramic layer in the carbon-coated aluminum foil roll was 1.6 ± 0.2 μm, the surface roughness Ra was 0.32 μm, the carbon coating layer was undamaged, and the coating adhesion reached level 5B. After continuous coating of 800,000 meters, the attenuation of the printing roller's screen depth was only 1.8 μm, still meeting the usage requirements.
[0048] Example 2 Carbon-coated aluminum foil with a thickness of 15μm and a double-sided carbon coating thickness of 2μm was selected. A Φ200mm full-width coating roller (25μm screen depth, 280 lines / inch, electroplated hard chrome working layer 02, hardness HV950) with the same specifications as in Example 1 was used for coating in the direction of travel, with an included angle of 4°, a speed ratio of 1.0:1, and a strip travel speed of 40m / min.
[0049] Preparation of PVDF adhesive: By weight, 12 parts PVDF resin (functional component), 1 part bentonite thixotropic agent, 1 part wetting and dispersing agent, and 86 parts N-methylpyrrolidone (NMP) solvent were mixed evenly. The resulting PVDF adhesive had a viscosity of 800 cps, a thixotropic index of 3.5, and a fineness of 2 μm. In this embodiment, the PVDF resin itself also has adhesive properties, so no separate adhesive is added to the formulation. Before coating, the surface of the strip was pretreated with plasma at a power of 600 W for 10 s. After coating, the strip was subjected to gradient drying by sequentially passing through a first temperature zone of 80℃ for 2 min and a second temperature zone of 100℃ for 2 min.
[0050] Testing revealed that the dry thickness of the adhesive layer of the carbon-coated aluminum foil roll was 1.6 ± 0.18 μm, the surface roughness Ra was 0.35 μm, the coating was uniform and free of crystal points, and the bonding strength was 22% higher than that of the reverse coating process.
[0051] Example 3 A 12μm thick aluminum foil with a 1.5μm double-sided carbon coating was selected. The foil width was 600mm, and the ceramic coating width at the target edge was 2.0mm. A Φ200mm selective coating roller was used. The width of coating area 04 was 2.8mm (including a 0.4mm trimming allowance). The uncoated area 05 had a mirror finish (surface roughness Ra not greater than 0.12μm). The mesh depth of coating area 04 was 25μm, the mesh count was 280 lines / inch, the mesh structure 03 was a frustum pyramid shape, the gradient transition zone width was 0.7mm, and the working layer 02 was an electroplated hard chrome layer with a hardness of HV950. Coating was performed in the same direction at a 4° angle, a speed ratio of 1.0:1, and a strip travel speed of 45m / min. The ceramic slurry formulation was the same as in Example 1.
[0052] The test results showed that the dry thickness of the ceramic layer at the edge of the carbon-coated aluminum foil roll was 1.25±0.15μm, the coverage width was 2.02±0.04mm, there was no leakage at the boundary, and the edge roughness Ra was 0.28μm.
[0053] Example 4 A 12μm thick aluminum foil with a 1.5μm double-sided carbon coating was selected. The foil width was 600mm, and the coating width at the target edge was 3.4mm. A Φ200mm selective coating roller was used. The width of coating area 04 was 3.8mm (including a 0.4mm trimming allowance), the uncoated area 05 had a mirror finish, the mesh depth of coating area 04 was 25μm, the mesh count was 280 lines / inch, and the working layer 02 was an electroplated hard chrome layer. Coating was performed in the direction of travel at a 4° angle, a speed ratio of 1.0:1, and a strip travel speed of 40m / min. The PVDF adhesive formulation was the same as in Example 2.
[0054] The test results showed that the dry thickness of the edge adhesive layer of the carbon-coated aluminum foil roll was 1.3±0.14μm, the coverage width was 3.21±0.04mm, there was no leakage at the boundary, and the edge was smooth without thick edges.
[0055] In summary, this invention achieves zero mechanical damage to the conductive carbon coating layer through the synergistic matching of the structural design of the forward-coating micro-gravure roller 10 and the forward-coating process parameters. On the one hand, the roller and the strip move in the same direction with similar linear velocities, eliminating the scraping and micro-cutting effects of reverse coating on the conductive carbon coating layer, and achieving zero mechanical damage to the carbon coating layer. On the other hand, the shallow mesh and high-line-count weave structure 03, combined with the high thixotropic properties of the adhesive, ensures complete transfer of the adhesive and a dense and uniform coating under forward-coating conditions, helping to eliminate defects such as flow marks, orange peel texture, pinholes, and material shortage streaks. Simultaneously, by replacing the full-width coating roller with the selective coating roller, flexible switching between full-width coating and edge selective coating can be achieved on the same coating equipment. It should be noted that the above embodiments are only used to illustrate the technical solution of this invention and not to limit it. Any modifications, equivalent substitutions, and improvements made by those skilled in the art within the spirit and principles of this invention should be included within the scope of protection of this invention.
[0056] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element.
[0057] The embodiments of the present invention have been described above with reference to the accompanying drawings. The disclosed embodiments are merely preferred embodiments of the present invention. However, the present invention is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many equivalent changes in form under the guidance of the present invention without departing from the spirit and scope of the claims. All such changes are within the protection scope of the present invention.
Claims
1. A method for preparing carbon-coated aluminum foil rolls, characterized in that, The preparation method includes the following steps: Step S1: Install the carbon-coated aluminum foil master roll with conductive carbon coating on both sides onto the unwinding shaft of the unwinding device, control the unwinding tension of the carbon-coated aluminum foil strip after it is unwound from the carbon-coated aluminum foil master roll to be 50~120N / m, and flatten the carbon-coated aluminum foil strip before it enters the coating station. Step S2: Obtain the adhesive and the unidirectional coating microgravure roller. The unidirectional coating microgravure roller includes a roller body and a working layer disposed on the surface of the roller body. The surface of the working layer is provided with a coating functional area. The surface of the coating functional area is engraved with a mesh structure. The mesh depth of the mesh structure is 12~30μm and the mesh line count is 200~300 lines / inch. The adhesive is supplied to the coating functional area, and the rotation direction of the unidirectional coating micro-gravure roller is set in the same direction as the travel direction of the carbon-coated aluminum foil strip. The adhesive is carried by the textured structure, and during the process of the unidirectional coating micro-gravure roller and the carbon-coated aluminum foil strip moving in the same direction, the adhesive is transferred to the conductive carbon coating surface on at least one side of the carbon-coated aluminum foil strip to form a wet adhesive coating. Step S3: The carbonized aluminum foil strip with the adhesive wet coating is fed into an oven and dried using a gradient heating method. During drying, the carbonized aluminum foil strip passes sequentially through a first temperature zone and a second temperature zone. The temperature of the first temperature zone is 70-100°C, and the residence time of the carbonized aluminum foil strip in the first temperature zone is 1-3 minutes to evaporate the solvent or moisture in the adhesive wet coating. The temperature of the second temperature zone is 80-150°C, and the residence time of the carbonized aluminum foil strip in the second temperature zone is 1-3 minutes to allow the adhesive wet coating to crosslink and cure, forming a functional coating. Step S4: Inspect the dried carbon-coated aluminum foil strip and rewind the qualified carbon-coated aluminum foil strip to obtain carbon-coated aluminum foil roll.
2. The method for preparing carbon-coated aluminum foil rolls according to claim 1, characterized in that, The unidirectional micro-gravure roller is a full-width coating roller, and the textured structure is uniformly distributed along the axial direction of the working layer within the coating functional area; the adhesive wet coating covers the entire coating area of the carbon-coated aluminum foil strip.
3. The method for preparing carbon-coated aluminum foil rolls according to claim 1, characterized in that, The unidirectional coating microgravure roller is a selective coating roller. The surface of the working layer is divided along the axial direction of the unidirectional coating microgravure roller into an uncoated area located in the middle of the unidirectional coating microgravure roller and a coating area located on both sides of the uncoated area. The surface of the coating area is engraved with the mesh structure, and the surface of the uncoated area is a mirror structure with a roughness of less than or equal to 0.15μm. At the boundary between the coating area and the uncoated area, a gradient transition zone with a gradually changing mesh depth is provided. The mesh depth in the gradient transition zone gradually decreases from the mesh depth of the coating area towards the uncoated area along the axial direction of the unidirectional coating micro-gravure roller to zero. During coating, the coating area transfers the adhesive to both sides of the carbonized aluminum foil strip, forming a blank area in the middle of the carbonized aluminum foil strip that is not coated with the adhesive.
4. The method for preparing carbon-coated aluminum foil rolls according to claim 1, characterized in that, Step S2 includes the following steps: adjusting the angle between the axis of the unidirectional coating microgravure roller and the plane where the carbon-coated aluminum foil strip is located to 2~8°, controlling the ratio of the linear velocity of the unidirectional coating microgravure roller to the linear velocity of the carbon-coated aluminum foil strip to be 0.9~1.1:1, and the traveling speed of the carbon-coated aluminum foil strip to be 15~60m / min.
5. The method for preparing carbon-coated aluminum foil rolls according to claim 1, characterized in that, The diameter of the unidirectional coating microgravure roller is 150~220mm, and the dynamic balance quality grade of the unidirectional coating microgravure roller is greater than or equal to G6.
3.
6. The method for preparing carbon-coated aluminum foil rolls according to claim 1, characterized in that, The working layer has a thickness of 50~200μm and a hardness greater than or equal to HV950.
7. The method for preparing carbon-coated aluminum foil rolls according to claim 1, characterized in that, The adhesive has a viscosity of 200~3500cps, a thixotropic index of 2~7, and a fineness of ≤5μm; wherein the thixotropic index is the ratio of the viscosity at 6rpm to the viscosity at 60rpm under the same conditions.
8. The method for preparing carbon-coated aluminum foil rolls according to claim 1, characterized in that, Before step S2, the adhesive is prepared. The adhesive comprises 10-55 parts by weight of functional components, 5-30 parts by binder, 0.3-3 parts by thixotropic agent, 0.5-2.5 parts by wetting and dispersing agent, and the balance being deionized water or organic solvent, wherein the sum of the weight parts of each component is 100 parts.
9. The method for preparing carbon-coated aluminum foil rolls according to claim 8, characterized in that, The functional component is one or more of ceramic powder, polyvinylidene fluoride resin, or acrylic resin; the thixotropic agent is hydroxyethyl cellulose or bentonite.
10. A carbon-coated aluminum foil roll, characterized in that, The carbon-coated aluminum foil roll is made by the method for preparing carbon-coated aluminum foil roll as described in any one of claims 1-9.